Ethnobotany of Artistic Plant Uses. - Marín, Jon; Garnatje, Teresa; Vallès, Joan (Ethnobiology Letters, 2024)
Artistic uses of plants are rarely explored in ethnobotanical studies. However, in Baix Llobregat (Catalonia, NE Iberian Peninsula), seeds and other plant parts are utilized to create art expressions associated with agricultural fairs and promotion of local vegetal goods. The objective of this study is to catalog the plants used and evaluate the current vitality and importance of this cultural and social activity. The methodology employed involved semi-structured interviews and observation. We have identified two distinct types of artistic creations. A total of 65 taxa have been identified, primarily comprising locally cultivated species. The results of this research emphasize the enduring presence of ethnobotanical knowledge related to cultural uses and underscore the importance of its preservation.